Pengaruh Kultur Kantor Akuntan Publik terhadap Komunikasi dalam Tim Audit - Nugraheni, Peni (Universitas Muhammadiyah Yogyakarta, Indonesia, 2005)
This research examines the effect of the Public Accountant Firm (KAP) culture in audit team communication. The samples used in this study is accountant publics ever or joining in audit team for certain duty with working experience between three up to five years in the KAP audit division. The samples consist of 118 accountant publics from 50 KAP in 8 cities at Java Island and Bali. The proxies for KAP culture are bureaucracy, inovatif and suportif culture. The result indicate that bureaucracy and suportif culture significantly influence the audit team communication. TheÂ result have implication to KAP about how to create the right culture to support the success of audit team communication in resulting a quality audit opinion.